The Characteristics of Vibration Isolation System with Damping and Stiffness Geometrically Nonlinear - Lu, Ze-Qi; Chen, Li-Qun; Brennan, Michael J. [UNESP]; Li, Jue-Ming; Ding, Hu (IOP Publishing, 2016)
The paper concerns an investigation into the use of both stiffness and damping nonlinearity in the vibration isolator to improve its effectiveness. The nonlinear damping and nonlinear stiffness are both achieved by horizontal damping and stiffness as the way of the geometrical nonlinearity. The harmonic balance method is used to analyze the force transmissibility of such vibration isolation system. It is found that as the horizontal damping increasing, the height of the force transmissibility peak is decreased and the high-frequency force transmissibility is almost the same. The results are also validated by some numerical method. Then the RMS of transmissibility under Gaussian white noise is calculated numerically, the results demonstrate that the beneficial effects of the damping nonlinearity can be achieved under random excitation.